USE OF PHRASEOLOGICAL UNITS WITH THE COMPONENT «DOG» IN LITERARY WORKS - Amaniyazov, Allayar Oralbaevich (SCIENCE and SOCIETY, 2026)
The article provides an overview of the scholarly opinions expressed in works related to phraseology. At the same time, the semantic and colloquial features of phraseological units related to dogs were discussed, and their meanings in literary works were analyzed.